2019
DOI: 10.1111/hsc.12798
|View full text |Cite
|
Sign up to set email alerts
|

Does older adults’ use of social care influence their healthcare utilisation? A systematic review of international evidence

Abstract: Improving our understanding of the complex relationship between health and social care utilisation is vital as populations age. This systematic review aimed to synthesise evidence on the relationship between older adults’ use of social care and their healthcare utilisation. Ten databases were searched for international literature on social care (exposure), healthcare use (outcome) and older adults (population). Searches were carried out in October 2016, and updated May 2018. Studies were eligible if they were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Associations between care home residence and reduced end-of-life ED attendance have been identified in the literature [ 6 ], but not variation by care home type. The potentially ‘protective’ effect of nursing homes has important policy implications and underlines the importance of timely clinical input in community care [ 34 ]. However, community care workforce capacity to support clinical continuity is tentative, with staff turnover in social care highest among registered nurses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Associations between care home residence and reduced end-of-life ED attendance have been identified in the literature [ 6 ], but not variation by care home type. The potentially ‘protective’ effect of nursing homes has important policy implications and underlines the importance of timely clinical input in community care [ 34 ]. However, community care workforce capacity to support clinical continuity is tentative, with staff turnover in social care highest among registered nurses [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have identified no evidence specific to community care services, but the literature on social care services suggests community care services could be a weak substitute for hospital services. A systematic review of the association between social care and hospital care conducted by Spiers et al [ 21 ] found no evidence on the number of social care users and A&E attendances in the UK [ 22 ] and weak substitute relationships between users of care homes and hospital admissions [ 23 , 24 ] and A&E attendances in the USA [ 23 ]. However, a study by Forder [ 25 ] assessed the relationship between long term care and hospital utilisation for older patients, finding them to be substitutes, with a £1 spend on social care leading to a £0.35 reduction in hospital expenditure.…”
Section: Methodsmentioning
confidence: 99%
“…The findings show community care contacts to be weak substitutes with all types of hospital activity and primary care contacts are weak substitutes for emergency hospital attendances and admissions. Our estimates ranged from 28 [95% CI 21, 45] to 517 [95% CI 291, 7265] community care contacts and from 34 [95% CI 17, 1283] to 1655 [95% CI − 1995 GP appointments to reduce one hospital service visit. Primary care and planned hospital services are complements.…”
mentioning
confidence: 99%
“…eligibility criteria and benefit package) in different countries (Bakx et al, 2015). Despite considerable evidence that formal care substitutes for informal care, only a few studies describe the association between public LTC and medical services (Gaughan et al, 2015;Spiers et al, 2019). Furthermore, such studies show mixed results that are not consistent (Spiers et al, 2019).…”
Section: Introductionmentioning
confidence: 99%